Transcriptomics reveal the involvement of reactive oxygen species production and sequestration during stigma development and pollination in Fraxinus mandshurica - Shuqi Wang; Shun Yang; Bello Hassan Jakada; Hongtao Qin; Yaguang Zhan; Xingguo Lan (Forestry Research)
Stigma development and successful pollination are essential for the continuous existence of flowering plants. However, the specific mechanisms regulating these important processes are not well understood. In this study, we investigated the development of the stigma in Fraxinus mandshurica, dividing it into three stages: S1, S2, and S3. Transcriptome data were used to analyze the gene expression patterns across these developmental stages, and 6,402 genes were observed to exhibit variable expression levels. Our analysis revealed a significant enrichment of pathways related to reactive oxygen species (ROS) and flavonoids, as indicated by the Kyoto Encyclopedia of Genes and Genomes enrichment analysis of the differentially expressed genes. Further examination by cluster analysis and quantitative polymerase chain reaction revealed that 58 genes were associated with ROS synthesis and seven genes were linked to flavonoid synthesis during the S2 and S3 stages. ROS accumulated during stigma development, which decreased rapidly upon pollen germination and pollen tube elongation, as confirmed by H2DCFDA staining. Moreover, ROS levels in mature stigmas were reduced by treatment with ROS scavengers, such as copper (II) chloride, sodium salicylate, and diphenyleneiodonium, an inhibitor of NADPH oxidases, which enhanced pollen adhesion and germination. These findings suggest that the balance between ROS production and sequestration plays a critical role in regulating stigma development and pollen germination in Fraxinus mandshurica.